2012
DOI: 10.1073/pnas.1203941109
|View full text |Cite
|
Sign up to set email alerts
|

Viral-induced encephalitis initiates distinct and functional CD103 + CD11b + brain dendritic cell populations within the olfactory bulb

Abstract: Dendritic cells (DC) are antigen-presenting cells found in both lymphoid and nonlymphoid organs, including the brain (bDC) of Cd11c/eyfp transgenic C57BL/6 mice. Using an intranasal vesicular stomatitis virus infection, we demonstrated that EYFP + cells amass in areas associated with viral antigens, take on an activated morphology, and project their processes into infected neuronal tissue within the olfactory bulb. These bDC separated into three EYFP … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
52
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 44 publications
(55 citation statements)
references
References 45 publications
3
52
0
Order By: Relevance
“…We next examined whether the circadian time of infection affects the cellular response to VSV in mice infected at ZT0 and ZT12. As described previously (20), cell populations isolated from VSV-infected OB contain brain-resident MG (CD45 (A-C) Circulating cytokine levels were measured using cytometric bead array. Data compiled from two independent experiments are expressed as mean ± SEM (total n = 6 per time point, two-way ANOVA, Bonferroni's posttest; *P < 0.05, **P < 0.01, ZT12 vs. ZT0).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…We next examined whether the circadian time of infection affects the cellular response to VSV in mice infected at ZT0 and ZT12. As described previously (20), cell populations isolated from VSV-infected OB contain brain-resident MG (CD45 (A-C) Circulating cytokine levels were measured using cytometric bead array. Data compiled from two independent experiments are expressed as mean ± SEM (total n = 6 per time point, two-way ANOVA, Bonferroni's posttest; *P < 0.05, **P < 0.01, ZT12 vs. ZT0).…”
Section: Resultsmentioning
confidence: 99%
“…Virus purification and the VSV LD 50 (7,000 pfu) for i.n. administration were determined in 5-to 7-wk-old male mice as described previously (20). For intranasal infection model see SI Materials and Methods.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Using transgenic mice expressing enhanced yellow fluorescent protein (eYFP) downstream of the DC-associated CD11c promoter (CD11c-eYFP), Bulloch et al described a discrete network of DCs within the healthy adult, developing, and aged mouse brain as well as during disease states including seizures, stroke, viral encephalitis, and in response to intracerebral (i.c.) cytokine injection (Bulloch et al, 2008, D'Agostino et al, 2012, Felger et al, 2010, Gottfried-Blackmore et al, 2009, Kaunzner et al, 2012). DCs are also thought to accumulate in the CNS during experimental autoimmune encephalomyelitis (EAE, a mouse model of multiple sclerosis), and we have shown that increasing the number of CNS DCs by i.c.…”
Section: Introductionmentioning
confidence: 99%
“…rabies, Ebola, and Hendra viruses) can be found in the Order Mononegavirales. These viruses can also have economic impacts because of their ability to infect poultry and cattle (D’Agostino et al, 2012b)Lamb and Parks, 2007; Lyles and Rupprecht, 2007; Planz et al, 2009). Vesicular stomatitis virus (VSV) is a member of the Vesiculovirus genus in the Rhabdoviridae family, one of the four families in the Order Mononegavirales and is the prototypic virus of this family that includes rabies virus.…”
Section: Introductionmentioning
confidence: 99%